Application of Pesticides Act 1974 in protecting community and environment health in Malaysia from the exposure of pesticides - Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2021)
Introduction: Pesticides are used to boost agricultural production in Malaysian farms in an effort to reduce or eliminate yield losses and maintain high produce quality. The high toxicity of these pesticides can be detrimental to public and environmental health. Thus, the issues of dumping of illegal pesticides in the market and being used by the farmer becoming a growing concern. To tackle this issues, Pesticides Act 1974 (Act 149) is enacted to regulate various aspects related to pesticide and applies throughout Malaysia. The Act covers the management of all pesticides and other chemicals used in agriculture. This paper discussed on the beneficial of Pesticide Act 1974 and elaborates of its strengthen and weaknesses. Secondary data are collected with regard to “Pesticides Act 1974”, “strengthen” and “weaknesses” of this act to protect community and environment. Pesticide poisoning in Malaysia is become the second major cause of poisoning group after pharmaceuticals. Thus, this Act has a strict control of the presence of pesticides in food, which the Board has the power to cancel the registration if it is found that the pesticides contain adverse effects on human beings, animals, plants, fruits or property due to their toxicity and inefficacy. On the other side, this Act still not effectively controlled the unregistered, smuggle and banned pesticide. The current Pesticides Act 1974 can do better amendment in future in order to tackle the unregistered pesticides issues by making more improvement to this Act so that the problems can be reduce or eliminate. In order to increase penalties and impose mandatory imprisonment and fines on the culprit, there must be a review of the Act to guarantee that the damage involved will be punished as the serious crime that it is.